A systematic review of the influence of radiation-induced lymphopenia on survival outcomes in solid tumors. (March 2018) - Venkatesulu, Bhanu Prasad; Mallick, Supriya; Lin, Steven H.; Krishnan, Sunil
Highlights: Radiation-induced reduction of circulating lymphocyte counts and eventual lymphocyte infiltration of tumors have a tangible impact on overall survival outcomes. Lymphocyte LD50 (lethal dose required to reduce the surviving fraction of lymphocytes by 50%) is 2 Gy and LD90 (lethal dose required to reduce the surviving fraction of lymphocytes by 90%) is 3 Gy. Unintentional irradiation of CL pools and secondary lymphoid organs are instrumental in causing lymphopenia. Strategies to evaluate and adopt radiation planning/treatment strategies such as proton therapy or spleen-sparing treatment plans to minimize RT-induced lymphopenia are the need of the day. Abstract: Lymphopenia is a common accompaniment of multimodal cancer therapy. As the most radiosensitive cells of the hematopoietic system, lymphocytes residing within or circulating through a radiation portal are frequently depleted by radiation therapy. The recognition that radiation-induced reduction of circulating lymphocyte counts and eventual lymphocyte infiltration of tumors have a tangible impact on overall survival outcomes has revived the interest in understanding the causes of treatment-associated lymphopenia and developing strategies to predict, prevent and ameliorate this well-documented phenomenon. In this systematic review, we have performed a comprehensive search of the literature to elucidate the studies that document a correlation between radiation-associated lymphopenia and survival outcomes in solid malignancies. We also summarize potential unifying paradigms that account for radiation-induced lymphopenia across studies and lay the groundwork for attempting to explain and/or counter this phenomenon.